Speak out or stay silent? A study of oil company-community relations through the political ecology of voice (Alternautas, 2022)
“[T]o try to lift the pipeline, we had to immerse in that water without any protection … under the instruction of engineers, they told us that we had to try to reach it, so we did immerse there without any clothing, only underwear and it was full of crude oil, it was thick” (A Cuninico indigenous resident in the Peruvian Amazon describes their 2014 oil spill remediation work)